Analisis Self Disclosure dengan Minat Layanan Konseling Siswa SMK - Hasanah, Annisa Uswatun; Setiyowati, Arbin Janu; Multisari, Widya (Universitas Muria Kudus, 2023)
Visits of counseling services for Adi Husada Health Vocational High School students have decreased for 2 last years from 44 students in 2019/2020 to 17 students in 2020/2021. The one of interest internal factors of students that encourage to participate in counseling services which is self disclosure to students. The purpose of this research is to review the relationship between a self disclosure variables and interest of counseling services. The self disclosure instrument was structured according to DeVito’s theory (1986) and the interest of counseling services was based on interest theory by Winkel’s (2010). This research method use a quantitative correlation research with simple random sampling technique with sample are 125 students. Self disclosure results obtained as much as 68% in high category and 98% in very high category. There is no relationship between two variables with correlation number of 0,068. The conclusion is a high self disclosure doesn’t determine a high interest in counseling services and a low self disclosure doesn’t determine a low interest in counseling services. As suggestion, for further research are use more variables that allow for relationship between self disclosure and interest in counseling services. And for counselors are be more active to offer the students about counseling services.